Federal government budget in brief, fiscal year 1982 - Shagari, Shehu Usman Aliyu; Akinyele, T. A. ([Lagos] : Federal Republic of Nigeria, 1982)
This brief contains a financial statement of the President of federal republic of Nigerian in the 1982. The highlights includes budget speech, budget estimates for various sector of the economy including capital and recurrent estimates.
"Analysis of the 1982 federal government budget, by Mr. T.A. Akinyele": p. 21-49.
asm; 15/04/19
Loans
Keywords: Budget